2014
DOI: 10.1371/journal.pone.0098143
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Blood-Brain Barrier Function and the Neuroinflammatory Response in the Rat Brain by Using Cerebral Open Flow Microperfusion (cOFM)

Abstract: Blood-brain barrier (BBB) impairment in systemic inflammation leads to neuroinflammation. Several factors including cytokines, chemokines and signal transduction molecules are implicated in BBB dysfunction in response to systemic inflammation. Here, we have adopted a novel in vivo technique; namely, cerebral open flow microperfusion (cOFM), to perform time-dependent cytokine analysis (TNF-alpha, IL-6 and IL-10) in the frontal cortex of the rat brain in response to a single peripheral administration of lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 58 publications
3
53
0
1
Order By: Relevance
“…These effects could be related to peripheral proinflammatory factors released by periodontal inflammatory mediators such as C-reactive protein, interleukin-6, haptoglobin, tumor necrosis factor-alpha, and fibrinogen [71,80,81]. Other studies have also shown that these proinflammatory factors may penetrate the blood-brain barrier, and that this may be the reason why local or systemic inflammatory mediators can influence the brain [82,83]. We, therefore, hypothesize that these proinflammatory factors may penetrate the blood-brain barrier during inflammatory conditions, resulting in neurodegenerative changes in the development of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…These effects could be related to peripheral proinflammatory factors released by periodontal inflammatory mediators such as C-reactive protein, interleukin-6, haptoglobin, tumor necrosis factor-alpha, and fibrinogen [71,80,81]. Other studies have also shown that these proinflammatory factors may penetrate the blood-brain barrier, and that this may be the reason why local or systemic inflammatory mediators can influence the brain [82,83]. We, therefore, hypothesize that these proinflammatory factors may penetrate the blood-brain barrier during inflammatory conditions, resulting in neurodegenerative changes in the development of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a bacterial endotoxin is widely used to mimic systemic inflammatory conditions with activation of glial cells (microglia and astrocytes) in brain to synthesize and secrete a variety of neuroactive and neurotoxic molecules, interleukins and free radicals (Henry et al 2008;Ghosh et al 2014). Activated astrocytes proliferate and produce a variety of inflammatory mediators such as nitric oxide (NO), TNF-a, etc.…”
Section: Introductionmentioning
confidence: 99%
“…144 Recently, it was demonstrated that acute injection of a septic dose of LPS intraperitoneally could lead to breakdown of the blood-brain barrier and increased brain levels of proinflammatory cytokines with activated microglia in an experimental model. 145 Systemic LPS (indirectly, by inducing blood-brain barrier epithelial cells or proinflammatory cytokine release) could activate microglia and cause neuroinflammation in the adult 142 and aged brain. 146,147 This may predispose to neurodegeneration, 142 whereas aging reduces the responsiveness to the interleukin 4-induced M2 microglia phenotype.…”
Section: Effects Of Leaky Gut and Intestinal And Systemic Inflammatiomentioning
confidence: 99%